Serum calcification propensity and its association with biochemical parameters and bone mineral density in hemodialysis patients - Hyunsook Kim; Ae Jin Kim; Han Ro; Jae Hyun Chang; Hyun Hee Lee; Wookyung Chung; Ji Yong Jung (The Korean Society of Nephrology, 2023)
Background T50 is a novel serum-based marker that assesses the propensity for calcification in serum. A shorter T50 indicates a greater propensity to calcify and has been associated with cardiovascular disease and mortality among patients with chronic kidney disease. The factors associated with T50 and the correlation between T50 and bone mineral density (BMD) are unknown in hemodialysis (HD) patients. Methods This cross-sectional study included 184 patients undergoing HD. Individuals were grouped into tertiles of T50 to compare the demographic and disease indicators of the tertiles. Linear regression was used to evaluate the association between T50 and hip and spinal BMD in a multivariate model. Results Mineral and inflammatory parameters, including serum phosphate (r = -0.156, p = 0.04), albumin (r = 0.289, p < 0.001), and high-sensitivity C-reactive protein (r = -0.224, p = 0.003) levels, were associated with T50. We found a weak association between T50 and BMD in the total hip area in the unadjusted model (β = 0.030, p = 0.04) but did not find a statistically significant association with the total hip (β = 0.017, p = 0.12), femoral neck (β = -0.001, p = 0.96), or spinal BMD (β = 0.019, p = 0.33) in multivariable-adjusted models. Conclusion T50 was moderately associated with mineral and inflammatory parameters but did not conclusively establish an association with BMD in HD patients. Broad-scale future studies should determine whether T50 can provide insights into BMD beyond traditional risk factors in this population.